2014
DOI: 10.3390/molecules190913358
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation on Nearsightedness of Finite Model and Molecular Systems Based on Linear Response Function Analysis

Abstract: Abstract:We examined nearsightedness of electronic matter (NEM) of finite systems on the basis of linear response function (LRF). From the computational results of a square-well model system, the behavior of responses obviously depends on the number of electrons (N): as N increases, LRF, δρ(r)/δv(r′), decays rapidly for the distance, |r−r′|. This exemplifies that the principle suggested by Kohn and Prodan holds even for finite systems: the cause of NEM is destructive interference among electron density amplitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 31 publications
4
13
0
Order By: Relevance
“…In fact, we previously confirmed their statement with inspecting linear response function (LRF) of density, (δρ(r)/δv(r )) N , which is the density responses at positions (δρ(r)) due to virtual perturbations at other points (δv(r )), for several model and molecular systems with the various numbers of electrons [7,8]. For instance, we showed that, for a one-dimensional (1D) square-well potential system and the hydrogen molecular system, the calculated LRFs were remarkably delocalised for two-electrons [8].…”
Section: Introductionsupporting
confidence: 51%
See 4 more Smart Citations
“…In fact, we previously confirmed their statement with inspecting linear response function (LRF) of density, (δρ(r)/δv(r )) N , which is the density responses at positions (δρ(r)) due to virtual perturbations at other points (δv(r )), for several model and molecular systems with the various numbers of electrons [7,8]. For instance, we showed that, for a one-dimensional (1D) square-well potential system and the hydrogen molecular system, the calculated LRFs were remarkably delocalised for two-electrons [8].…”
Section: Introductionsupporting
confidence: 51%
“…In fact, we previously confirmed their statement with inspecting linear response function (LRF) of density, (δρ(r)/δv(r )) N , which is the density responses at positions (δρ(r)) due to virtual perturbations at other points (δv(r )), for several model and molecular systems with the various numbers of electrons [7,8]. For instance, we showed that, for a one-dimensional (1D) square-well potential system and the hydrogen molecular system, the calculated LRFs were remarkably delocalised for two-electrons [8]. A remaining problem is, as the number of electrons increases from two, say, in molecules of hydrogen molecule, to hundreds or thousands, which are the typical number of electrons in large molecular systems that has been treated with QM/MM calculations in the field of quantum chemistry, which size does NEM start to hold for?…”
Section: Introductionsupporting
confidence: 51%
See 3 more Smart Citations